Experiences of Sexual Stigma in Medical Care Facility Encountered by Gay and Bisexual Men in Taiwan - Huang-Chi Lin; Yu-Ping Chang; Cheng-Fang Yen (Taiwanese Journal of Psychiatry)
Objectives: Sexual stigma toward gay and bisexual men (GBM) is common in medical care facility. But few studies have explored this topic in non-Western countries. We did this qualitative study which explored the experiences of GMB regarding sexual stigma during their visits to medical units in Taiwan and the strategies they used to reduce encounters with sexual stigma. Methods: Data from open and in-depth interviews with 26 GBM were analyzed through reflexive thematic analysis. Results: Six themes were identified: (a) anticipated concerns among GBM about seeking medical care; (b) personal or second-hand experiences of sexual stigma in medical settings; (c) uncertainty about standard medical practices; (d) responses to sexual stigma in medical settings; (e) how to prevent sexual stigma in medical settings; and (f) how medical personnel can provide lesbians, gays, bisexuals, transgenders, queer/questioning, and others (LGBTQ+)-friendly care. Conclusion: The participants’ narratives revealed experiences of sexual stigma in medical units; therefore, implementing interventions for reducing sexual stigma and enhancing healthcare equality for GBM is imperative.